Utilization of NTB Care Information Technology as a Public Complaint Media for West Nusa Tenggara - Rifaid, Rifaid; Hadi, Ayatullah; Hidayatullah, Hidayatullah; Subandi, Azwar (ARISTO, 2024)
This article tries to explain the use of information technology for the NTB Care application as a digital media for responding to public complaints. Three dimensions are measured to determine the effective implementation of NTB Care in resolving public complaint services: the Ease of Use dimension, the Trust dimension and the Reliability dimension. The research uses a comparative descriptive method with a qualitative approach and literature analysis by collecting data from official NTB government documents, the NTB Care data center, the NTB Care Website, the NTB care Facebook, and other literature related to NTB Care. The results showed that the use of the NTB Care application as a medium for responding to public complaints was good and received excellent public trust, but the obstacles faced were in the agency that became the goal of the problems raised by the community, the average response time for OPD in handling complaints that come in 1-120 days. There is no clarity regarding reports that have not been followed up on to be resolved. NTB Care is an application as a forum to accommodate the community's aspirations; then, the NTB Care admin will forward public complaints to the relevant agency or OPD based on the complaint problem who entered NTB Care.